UMPSA international mobility students celebrate farewell with cultural activities - Muhammad Zufli, Zuhari (UMPSA, 2025)
KUANTAN, 20 January 2024 – The Centre for International Relations (CIR), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), organised the Semester I Mobility Student Farewell Ceremony for the 2024/2025 academic year at Adena Beach Resort.